The Availability Heuristic Effect on Financial Performance of Small and Medium Enterprises in Nairobi, Kenya: The mediating role of Investment Decisions - Koech , Alex (African Journal of Education,Science and Technology (AJEST), 2021)
Heuristic behavior is an integral part of decision-making process which heavily influences the investor’s financial performance. This study sought to examine the direct effect of the Availability heuristic, on financial performance and also analyze the mediating effect of investment decisions on the relationship between Availability heuristic and financial performance of the SMEs in Nairobi County. A sample size of 382 SMEs was selected using stratified sampling approach. Data was collected using self-administered, structured questionnaires and items were grounded on a five-point Likert scale with data analysis being done using descriptive and inferential statistics. The hypotheses were tested using multiple regression models for the direct relationship and Hayes model was used to test the mediation relationship. The regression results showed that availability heuristics positively and significantly predicts the Financial performance of SMEs (β= .129, p< .05) and this relationship is partially mediated by Investment decisions (β = .093, p<.001, CI=0.035, 0.162). Theoretically, the study supported the incorporation of the key heuristic factor (availability), and investment decisions, where the outcome of the results indicated the significant relationship in achieving financial performance of SMEs. The future researchers ought to focus on the challenges that the investors face in the process of making investment decisions.